Pengembangan Karir Terhadap Kinerja Melalui Kepuasan Kerja Sebagai Variabel Intervening - Marniati Syam; Masdar Mas’ud; Budiandriani Budiandriani (Program Pascasarjana STIE Amkop Makassar, 2023)
This study aims to analyze the effect of career development on performance through job satisfaction as an intervening variable at the Bone District Fisheries Service. This study uses a descriptive-quantitative approach with a causal correlation type. The population used in this study were all employees at the Bone District Fisheries Service, totaling 44 people. The method of determining the sample is full sampling. Data were analyzed using path analysis. The results of the study concluded that (1) career development has an effect on employee performance at the Bone District Fisheries Service, (2) career development has an effect on employee job satisfaction at the Bone District Fisheries Service, (3) job satisfaction has an effect on employee performance at Bone District Fisheries Service , (4) career development influences performance through employee job satisfaction at Bone District Fisheries Service. Kata Kunci: career development, performance, job satisfaction